IL CIRCOLO DI CAMBRIDGE: DANTISMO E FOLLIA - Anna Maria Cotugno (Sinestesieonline, 2018)
The ten circles of Dante’s Inferno, with the words that clash in eternity, are the background to the thriller of the Spanish writer who draws copiously from the medieval source and dialogues with Dante through the mad mind of his protagonist who, within a perverse play of mirrors, the poet is identified and assumes the function of guiding the world that ill-lives.